The bidirectional relationship between physical exercise and social self-efficacy: a cross-lagged model analysis of the mediating role of peer acceptance - Zhao, Zexi; Li, Ruoyu; Ying, Zi; Yang, Aonan (Frontiers in Psychology, 2025)
ObjectiveSocial self-efficacy is a crucial indicator of college students’ mental health, yet the underlying mechanisms of how physical exercise influences it require deeper exploration. This study aimed to examine the relationship between physical exercise and social self-efficacy among college students through a longitudinal design and test the mediating role of peer acceptance.MethodsA three-wave longitudinal tracking design was employed with 758 undergraduates from Zhengzhou University, with surveys conducted at 3-month intervals. Data were collected using the Physical Activity Rating Scale, Social Self-Efficacy Scale, and Peer Acceptance Scale. Cross-lagged models and bootstrap methods were used for statistical analysis.Results① Significant bidirectional longitudinal predictive relationships existed between physical exercise and social self-efficacy (β = 0.19–0.24, p < 0.01; β = 0.13–0.16, p < 0.01); ② Peer acceptance played a significant longitudinal mediating role in their relationship, with T1 physical exercise predicting T3 social self-efficacy through T2 peer acceptance [β = 0.071, 95% CI = (0.038,0.108)], and T1 social self-efficacy predicting T3 physical exercise through T2 peer acceptance [β = 0.053, 95% CI = (0.025,0.084)].ConclusionPhysical exercise and social self-efficacy form a mutually reinforcing dynamic cycle, with peer acceptance serving as a key mediating mechanism. This study provides scientific evidence for enhancing college students’ social adaptation through creating positive peer environments.